2002
DOI: 10.1093/ajcn/75.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in subacute care

Abstract: Malnutrition reaches epidemic proportions in patients admitted to subacute-care facilities. Whether this reflects nutritional neglect in acute-care hospitals or is the result of profound illness is unclear. Nevertheless, strict attention to nutritional status is mandatory in subacute-care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
119
2
18

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(152 citation statements)
references
References 25 publications
13
119
2
18
Order By: Relevance
“…Using MNA, Persson et al 31 report similar prevalences of PEM (26%) and moderate PEM or at risk of being PEM (56%) among Swedish geriatric patients as found in our study. Thomas et al 32 describe malnutrition to have reached epidemic proportions in a sub-acute care facility in St. Louis, USA, with the prevalence of either malnourished or at risk of malnutrition among its geriatric patients reported as more than 90%, a figure similar to that in the present study. Among studies of non-institutionalised elderly persons in the USA and Europe, the prevalence of nutritional risk is reported to range between 18% and 41%, whereas none were found to suffer from malnutrition 33 -35 .…”
Section: Who Are Undernourished?supporting
confidence: 86%
“…Using MNA, Persson et al 31 report similar prevalences of PEM (26%) and moderate PEM or at risk of being PEM (56%) among Swedish geriatric patients as found in our study. Thomas et al 32 describe malnutrition to have reached epidemic proportions in a sub-acute care facility in St. Louis, USA, with the prevalence of either malnourished or at risk of malnutrition among its geriatric patients reported as more than 90%, a figure similar to that in the present study. Among studies of non-institutionalised elderly persons in the USA and Europe, the prevalence of nutritional risk is reported to range between 18% and 41%, whereas none were found to suffer from malnutrition 33 -35 .…”
Section: Who Are Undernourished?supporting
confidence: 86%
“…Such finding suggests that it may be not necessary to fulfil more than the two subjective questions to screen as not having undernutrition in a very high percentage of community-dwelling elderly population. It is assumed that in a clinical setting, like a hospital, nursing home, etc., where it is expected an undernutrition prevalence higher than among free-living elderly Kagansky et al, 2005;Mowe, 2002;Pauly et al, 2007;Thomas et al, 2002), the proportion of discard subjects will be lower. Therefore, more studies are needed to demonstrate it.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since Dr Charles Edwin Butterworth Jr's seminal 1974 article "The Skeleton in the 41 Hospital Closet", there has been a positive movement in clinical health care to address Nutrition screening and nutrition assessment are essential parts of the nutrition care process, 48 as accurate identification and diagnosis of malnutrition is required in order for patients to be 49 adequately treated, and for nutrition resources to be used efficaciously [4]. However, it is 50 essential that the nutrition screening tools and nutrition assessment tools used to complete 51 these steps have undergone adequate evaluation for validity so that the most appropriate tool 52 can be selected for the patient group [2].…”
Section: Introductionmentioning
confidence: 99%
“…America or Africa, and only one study reported the prevalence in North America [48]. Only 275 two studies, both Australian, reported the prevalence of malnutrition in a rural population, 276 where the prevalence was high but varied according to type of nutrition assessment 277 (SGA=65% in one sample; ICD-10-AM criteria=46%, Scored PG-SGA=53%, MNA=28% in 278 a second sample) [38,56].…”
mentioning
confidence: 99%